An Algorithm for Computing Values of Options on the Maximum or Minimum of Several Assets - Boyle, Phelim P.; Tse, Y. K. (Journal of Financial and Quantitative Analysis, 1990)
An approximate method is developed for computing the values of European options on the maximum or the minimum of several assets. The method is very fast and is accurate for parameter ranges that are often of the most interest. The approach casts the problem in terms of order statistics and can be used to handle situations where the initial asset prices, the asset variances, and the covariances are all unequal. Numerical values are given to illustrate the accuracy of the method.